Mine Road Geometric Feasibility Study Pt Mahakam Sumber Jaya Uses Manual Method Of Road Pavement Design (Mdpl) - Yulfadli, Zony; Sasmoko Adi , Ari; Hermawan , Rudi (JSE Journal of Science and Engineering, 2025)
Abstract – The operational road section of PT Mahakam Sumber Jaya is a supporting tool for coal production operational activities located in Separi, Kutai Kartanegara. This study plans the geometric design and thickness of the road pavement. It attempts to review the geometric planning referring to the Bina Marga standards and re-planning using Auto CAD Civil 3D software, which is commonly used in geometric road planning, while the thickness planning of the pavement usually employs component analysis methods; however, I am re-planning using the Manual Pavement Design Method of 2024. The geometric planning of the road includes horizontal and vertical alignments, while the pavement thickness planning includes the detailed planning of rigid pavement structures. From the geometric planning results with a road length of 4.539 km, a pavement width of 2 x 3.5 m, a total of 7 curves, and a thickness of 300 mm concrete with a concrete quality of Fs 4.5 MPa, layers Foundation thickness 150 mm, LPA class A 200 mm, and selected coarse granular embankment 200 mm